The influence of school principal leadership, school support, and work motivation on teachers' professional competence - Hazimah Dzikra Hayati; Nellitawati Nellitawati; Lusi Susanti; Rusdinal Rusdinal (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study examined the influence of principals’ instructional leadership, school support, and work motivation on teachers' professional competence in Padang City’s public junior high schools. A sample of 385 teachers was selected, and data were analyzed using PLS-SEM. The results revealed that instructional leadership (β = 0.308, p < 0.05) and school support (β = 0.414, p < 0.05) positively impacted teachers' professional competence. Both instructional leadership (β = 0.359, p < 0.05) and school support (β = 0.434, p < 0.05) also significantly influenced work motivation, which in turn enhanced professional competence (β = 0.467, p < 0.05). The study highlights the critical role of leadership and support in fostering motivated teachers, offering practical implications for policymakers and school administrators aiming to improve teacher quality.